Cervical disc arthroplasty: What we know in 2020 and a literature review - Shin, Jun Jae; Kim, Kwang-Ryeol; Son, Dong Wuk; Shin, Dong Ah; Yi, Seong; Kim, Keung-Nyun; Yoon, Do-Heum; Ha, Yoon; Riew, K Daniel (Journal of orthopaedic surgery (Hong Kong), 2021)
Cervical disc arthroplasty (CDA) is a safe and effective option to improve clinical outcomes (e.g., NDI, VAS, and JOA) in degenerative cervical disc disease and compressive myelopathy. CDA’s two main purported benefits have been that it maintains physiologic motion and thereby minimizes the biomechanical stresses placed on adjacent segments as compared to an ACDF. CDA might reduce the degeneration of adjacent segments, and the need for adjacent-level surgery. Reoperation rates of CDA have been reported to range from 1.8% to 5.4%, with a minimum 5-year follow-up. As the number of CDA procedures performed continues to increase, the need for revision surgery is also likely to increase. When performed skillfully in appropriate patients, CDA is an effective surgical technique to optimize clinical outcomes and radiological results. This review may assist surgical decision-making and enable a more effective and safer implementation of cervical arthroplasty for cervical degenerative disease.